PENGARUH TEKANAN EKSTERNAL DAN AGRESIVITAS PAJAK TERHADAP KECURANGAN LAPORAN KEUANGAN - Siti Devi Avianita; Meutia Riany (UNIVERSITAS DHARMAWANGSA, 2026)
Financial statement fraud is a serious and frequent problem, especially in manufacturing companies in the food & beverage sub-sector listed on the Indonesia Stock Exchange (IDX). In such circumstances, increased external pressure and aggressive taxation practices can potentially lead to fraud in financial statements. This study aims to analyse the influence of external pressure and tax aggressiveness on the risk of financial statement fraud in manufacturing companies in the food & beverage subsector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2024. This study uses a quantitative approach with a panel data regression method. The data used is secondary data obtained from annual reports and complete sustainability reports. Financial statement fraud is measured using the Beneish M-score, external pressure using leverage, and tax aggressiveness using the Effect Tax Rate (ETR). The research sample consisted of 24 companies using purposive sampling with a total of 120 samples used. The results of this study indicate that external pressure and tax aggressiveness do not have a significant effect on financial statement fraud.